Introduction to Neutrosophic BCI/BCK-Algebras - A. A. A. Agboola; B. Davvaz (International Journal of Mathematics and Mathematical Sciences)
We introduce the concept of neutrosophic BCI/BCK-algebras. Elementary properties of neutrosophic BCI/BCK algebras are presented.